Gambaran Perilaku Hidup Sehat Pasien Hipertensi Rawat Jalan di Puskesmas Temajuk - Pane, Mustika Dewi; Rambe, Muhammad Arsyad Elfiqah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Behavior is an action that can be observed and has a specific frequency, duration and purpose both consciously and unconsciously. One of the efforts to prevent hypertension and other non communicable diseases recommended by the Government is by implementing the CERDIK program (regular health checks, Get rid of cigarette smoke, Diligent physical activity, Balanced diet, Adequate rest, and Manage stress). This study aims to describe the healthy behavior of outpatient hypertension at the Temajuk Health Center. This study used a descriptive quantitative design, with a total sample of 223 people using purposive sampling method. The results of this study indicate that based on exposure to cigarette smoke, the majority were high, namely 134 people (60.1%), based on physical activity, the majority were not sufficient, as many as 129 people (57.8%), based on eating and drinking habits, the majority were not good, as many as 134 people (60 .1%), based on the stress level, the majority of them had mild stress, as many as 88 people (39.5%). Based on the results of this study, it is hoped that people with hypertension will take better care of their health, especially in terms of smoking, physical activity, and a balanced diet.